Análise comparativa dos sistemas de instrumento único Reciproc, Waveone e One Shape na incidência de defeitos dentinários - Pillar, Rafael (2013)
Dentinal defects are characterized by cracks in the root dentin that can develop into a vertical root fractures (VRF), thus leading to tooth loss. Endodontic procedures may generate these defects and between these steps, the biomechanical preparations with NiTi rotary instruments are associated with the incidence of these amendments dentinal. A new concept in minimally invasive preparation was introduced, along with a new reciprocating movement, using a single instrument for root canal instrumentation. This allows less root dentin is removed, thus avoiding the weakening of tooth structure. The aim of this study was evaluate the incidence of dentinal defects after root canal preparation by three single-file systems. One hundred forty mesial roots of mandibular molars were selected and randomly assigned to 4 groups (n= 35 mesial roots per group). One group was left unprepared as control. In two groups, the root canals were instrumented by using the reciprocating single-file systems WaveOne (Dentsply-Maillefer) and Reciproc (VDW), while other group was prepared with single-file of continuous rotation One Shape (Micro-Mega). The specimens were sectioned in 03, 06 and 09 mm from the apex with a low-speed saw under water cooling (IsoMet 1000 Precision Saw) and observed through a stereomicroscope (Zeiss Stemi SV6, Carl Zeiss) at a magnification of 20×. The pictures were recorded and evaluated by two blinded calibrated observers. The slices were categorized in: 0- No defects; 1- Others defects and 2 vertical root fracture. The dates were statistically analyzed with a significance level set at α = 0.05. The chi-square and Fisher exact tests were used to assess the differences between groups. No defects were observed in control group. All the experimental groups showed dentinal defects. The reciprocating files were associated with more defects than the continuous rotary file and control group (P < 0.05), but no significant difference between them (P = .115). VRF was observed only in the One Shape group. The results of this study suggest that the biomechanical preparation could cause damage in the root dentin and that the continuous rotary has a tendency to result in fewer defects compared to reciprocating files.